Cartoon Dave's no-rules cartooning - Hackett, Dave (Camberwell, Vic. Puffin Books, 2004)
Great tips, techniques and trade secrets for creating all the characters you could ever imagine. (Adapted from back cover
Keywords: Cartooning -- Technique -- Juvenile literature. Caricatures and cartoons -- Juvenile literature. Caricatures and cartoons